The relationship between organizational initiatives and employee performance: a finding in Batu Pahat District Office / Rahaida Misnon - Misnon, Rahaida (2012)
The study sought to determine the relationship between the organizational initiatives and employee performance and to investigate which of the organizational initiatives have a moderate relationship with the employee performance. Basically, the study was done in the government service department in Batu Pahat particularly at Batu Pahat District Office. Tis study will be conducted by distributing questionnaires to 65 employees of Batu Pahat District Office. The target respondents will be ranked from the highest level officer to driver. The data that will be collected will be analyzed using the Multiple Regression and also using the Statistical Package for the Social Science (SPSS) software. The finding will reveal that organizational initiatives (technology, reward and recognition, leadership characteristics, training, and decision making) had a significant and positive relationship with the employee performance. Hence, this study can stimulate the organization in improving the employee performance of the staff in the Batu Pahat District Office.